he role of sports media (traditional and electronic) according to the gatekeeper theory in my project of female sports from the viewpoint of the teaching staff in the Faculties of Physical Education and Sports Sciences in Iraq - م. د علي عطيه عواد ا.م. د سندس موسى جواد (الرياضة المعاصرة)
The current conditions that society went through, and the changes that occurred in the country from the events of wars and the entry of many political systems, which affected the accepted concepts, so dealing with the concepts became sloppy, and as a result of weak security and changing governments, there has been a loss of credibility, regardless of the surrounding conditions. And the fluctuations of conditions that led to the disturbance of the values ​​of individuals, and the lack of credibility, as the flags are linked to society, as it directly affects social systems, culture, and sports organizations prevailing in society. My role in spreading sports culture among women? 2- What is the role of television in raising awareness of practicing sport 3-: What is the role of the sports program in increasing women's sports awareness?